1972
DOI: 10.1037/h0033973
|View full text |Cite
|
Sign up to set email alerts
|

Cross-validational studies of the personality correlates of the A-B therapist "type" distinction among professionals and nonprofessionals.

Abstract: Research with the A-B therapist "type" variable has included many analogue studies in which A and B undergraduates have been assumed to be personologically similar to A and B professionals. To assess whether this "invariance assumption" is tenable across samples varying in vocational commitment/ training, sex, education, and adjustment,, the present study cross-validated the personality correlates of A-B status (identified in a prior study with Jackson's Personality Research Form) across five new samples. A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1976
1976
1984
1984

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…I n line with Lorr and McNair's speculations about the meaning of these sex differences, some researchers, notably Berzins et al (1969), Berzins, Barnes, Cohen, & Ross (1971), Berzins et al (1972), Dublin et al (1969), and Goodwin et al (1973), have theorized that one of the dimensions that underlies the A-B scale is a masculinity -femininity variable and have interpreted their results to be congruent with this conceptualization, even though other interpretations may be more germane. The manifest advantages of such an approach are two-fold.…”
Section: Discussionmentioning
confidence: 84%
“…I n line with Lorr and McNair's speculations about the meaning of these sex differences, some researchers, notably Berzins et al (1969), Berzins, Barnes, Cohen, & Ross (1971), Berzins et al (1972), Dublin et al (1969), and Goodwin et al (1973), have theorized that one of the dimensions that underlies the A-B scale is a masculinity -femininity variable and have interpreted their results to be congruent with this conceptualization, even though other interpretations may be more germane. The manifest advantages of such an approach are two-fold.…”
Section: Discussionmentioning
confidence: 84%
“…With therapists, the direction of the interactions suggested that non-complimentary dyads (As with TAS and Bs with AVOS; cf. Berzins & Seidman, 1969;Lynch, Kogut, & Smith, 1976) were associated with longer responses, F( 1, 32) = 6.66, p <.05. The quasi-therapist, however, displayed the opposite A-B status X patient type relationship, F(1, 32) = 4.96, p <.05; the quasi-therapists group means suggested that complimentary pairings were associated with greater length of response.…”
Section: Resultsmentioning
confidence: 92%
“…The scale was scored in the B direction; high scores indicated B status, and low scores indicated A status. The upper and lower quartiles found in a normative sample of combined students and professional therapists were used as a determination of A-B status (Berzins et al, 1972). The mean score differences for the A-type therapist and quasi-therapist were not significantly different, nor were the scores between the B-type therapist and the B-type quasi-therapist.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations